An investigation of the relationship and pathways of influence between body mass index, motor coordination, and health-related physical fitness index in preschool children - Zhao, Deqiang; Chen, Xiaoxiao; Zhang, Aoyu; Wang, Chunmiao; Wang, Yibei; He, Jin; Chen, Jiaxin; Hu, Haixia; Tang, Xiaoni; Zhang, Aiying; Xiao, Han; Zhang, Yanfeng (Frontiers in Public Health, 2025)
BackgroundMovement development and motor ability are related to preschool children's physical health, and obesity is an increasingly serious problem in early childhood.ObjectiveThe aim of this study was to analyze the mechanism of body mass index (BMI), motor coordination (MC), and physical fitness index (PFI) influencing pathways and to provide theoretical references for promoting the health management of preschool children.MethodsA total of 374 preschool children aged 3–6 years from a kindergarten in Weifang City, Shandong Province, China, were recruited to this study using a stratified random sampling method. We evaluated the motor coordination of these preschool children through the Movement Assessment Battery for Children, Second Edition (MABC-2) and assessed the physical fitness index of their sports performance through physical fitness tests such as standing long jump and continuous two-foot jumping. Pearson correlation analysis, network analysis, and hierarchical regression analysis were used to verify the interaction between BMI, MC, and PFI at each level. Finally, the bootstrap method was used to test the mediating effect of motor coordination.ResultsThe results of the network analysis indicated that body mass index negatively affected preschoolers' motor coordination and physical fitness index. The stratified regression results indicated that body mass index negatively influenced physical fitness index (p < 0.01) and motor coordination positively influenced it (p < 0.01). Movement coordination played a mediating role (95% CI = [−0.077, −0.015]).ConclusionsThis study, based on cross-sectional data analysis, reveals the interrelationship between BMI, MC, and PFI in preschool children. BMI is significantly negatively correlated with MC and PFI, suggesting that lower MC and PFI may be associated with higher BMI levels. MC mediates the relationship between BMI and PFI, and improving motor coordination can weaken the negative association between BMI and PFI. Therefore, in promoting the sports health of preschool children, instead of simply increasing the amount of physical activity, training in motor coordination can be added to improve their sports performance.